Association between KRAS, NRAS, and BRAF mutations and tumor localization in colorectal cancer patients in BSMMU - Siddiquee, Muhammad Ali; Rahman, Shihab Al Mashiur; Islam, M. Shahidul; Ovi, Mir Rasekh Alam; Jalal, Muhammed Tanvir; Haque, Asif Almas; Saha, Kalyan Kumar; Hossain, Tasmina; Ali, M. Sumon; Akter, Joynab (International Surgery Journal, 2024)
Background: Colorectal cancer (CRC) is a common malignancy with significant genetic heterogeneity. Mutations in proto-oncogenes such as KRAS, NRAS, and BRAF play a pivotal role in CRC development, impacting prognosis and treatment. This study aims to correlate mutations in these genes with tumor localization in both primary and metastatic CRC in the Bangabandhu Sheikh Mujib medical university (BSMMU) cohort. Methods: This prospective cross-sectional study was conducted between July 2023 and June 2024 at BSMMU. A total of 30 CRC patients, confirmed via histopathology, were included. Purposive sampling was used to select patients. Tumor tissue samples were collected and analyzed for KRAS, NRAS, and BRAF mutations using DNA isolation, PCR amplification, and sequencing techniques. Results: Among the 30 patients, the majority were male (66.7%) with a mean age of 50.4 years. KRAS mutations were found in 5 patients (16.7%), while no mutations in NRAS or BRAF were detected. Rectal cancer was the most frequent tumor location (36.7%), followed by hepatic and splenic flexure (16.7% each). No significant correlation was observed between KRAS mutations and tumor localization​. Conclusions: There was no statistically significant correlation between KRAS, NRAS, and BRAF mutations and tumor localization in the BSMMU CRC patient cohort. The study highlights the need for larger sample sizes to better understand the genetic landscape of CRC in Bangladesh​. Small sample size may limit the ability to detect significant associations. Further large-scale studies could offer more conclusive insights.